Legal Litigation Assistance and Its Role in Strengthening Public Services in the Provincian Government of Bali - I Komang Adi Saputra; Putu Eva Ditayani Antari (Universitas Negeri Gorontalo, 2026)
This study aims to analyze the role of the Legal Bureau of the Regional Secretariat of Bali Province in providing legal assistance through litigation as a form of public service. The legal assistance provided includes providing legal advice, preparing legal documents, representation in court, and harmonizing policies between agencies. The research method uses a descriptive qualitative approach through literature study, observation, and interviews with related parties. The results showed that the legal assistance provided was responsive to ongoing disputes and proactive in preventing potential legal problems through risk analysis and policy recommendations. The effectiveness of legal assistance is supported by appropriate litigation strategies, regular monitoring, and cross-agency coordination. However, there are challenges in terms of improving the competence of human resources and utilizing information technology for case management. This study recommends strengthening human resource capacity through continuous training, optimizing digital-based litigation systems, and expanding studies on non-litigation aspects in future research to provide a more comprehensive perspective.